Severe Hypotony Maculopathy in Anterior Uveitis Associated with Hodgkin Lymphoma. (3rd April 2021) - Marchese, Alessandro; Giuffrè, Chiara; Miserocchi, Elisabetta; Cicinelli, Maria Vittoria; Bandello, Francesco; Modorati, Giulio
ABSTRACT: Purpose : To describe the clinical course and management of anterior uveitis complicated by ocular hypotony associated with Hodgkin lymphoma. Design : Case report. Methods : Chart and multimodal imaging review, including ultrasound biomicroscopy, widefield fundus pictures, fundus autofluorescence, fluorescein angiography, and indocyanine green angiography. Results : A 44-year-old female with progressive visual deterioration and history of low-grade fever developed bilateral granulomatous anterior uveitis complicated by severe hypotony maculopathy, not improving with systemic and topical steroids. After starting ibopamine 2% eye drops, ocular hypotony progressively resolved with visual recovery. Histologic examination of a biopsied enlarged lymph node of the neck revealed the presence of Hodgkin lymphoma, for which the patient underwent systemic chemotherapy. Conclusion : Severe hypotony maculopathy complicating anterior uveitis can be associated with Hodgkin lymphoma. Topical ipobamine 2% was safe and effective in the treatment of ocular hypotony in this case.